Influence of Energy State of Montmorillonite Interlayer Cations on Organic Intercalation - Limei Wu; Shiyue Cao; Guocheng Lv (Advances in Materials Science and Engineering)
It is well known that the intercalation of montmorillonite (Mt) with organic cations is a fast process. During the intercalation, the interaction between the original cations and the structure layer of Mt keeps changing, and the basal spacing of Mt keeps increasing until an organic environment has been built in the interlayer. Many properties of Mt also change during the intercalation, such as hydrophobic or hydrophilic property and thermal stability. In this research, the impact of intercalation on the properties of Mt was studied by investigating the change in basal spacing and energy that coordinates the interlayer cations during the intercalation of Mt with organic cations. The interaction between interlayer cations and the layers in the Mt structure and the change in the system energy were obtained by using molecular dynamics simulation. All the experiment and calculation results provide a theoretical proof in organic intercalation mechanism.